Giant ultrafast optical nonlinearities of annealed Sb2Te3 layers. Issue 4 (5th March 2020) - Moisset, Charles; Verrone, Richard-Nicolas; Bourgade, Antoine; Zeweldi, Gebrehiwot Tesfay; Minissale, Marco; Gallais, Laurent; Perrin-Pellegrino, Carine; Akhouayri, Hassan; Lumeau, Julien; Natoli, Jean-Yves; Iliopoulos, Konstantinos
Abstract : The optimization of a Sb2 Te3 thin film structure in order to obtain giant ultrafast nonlinearities is presented. Abstract : The optimization of thin Sb2 Te3 films in order to obtain giant ultrafast optical nonlinearities is reported. The ultrafast nonlinearities of the thin film layers are studied by the Z-scan technique. Giant saturable absorption is obtained, which is the highest ever reported, by means of the Z-scan technique.